The Effect of Hybrid Teaching Strategy via Mobile Applications in Education on Students' Mathematics Achievement - Khaled Ahmed Aqeel Alzoubi (Journal of Research in Mathematics, Science, and Technology Education, 2025)
In our digital age, traditional teaching methods have become unattractive to students, making education that combines interactive visual media, audio media, and collaborative media in a hybrid form provide an engaging and effective learning experience. This research highlights the impact of the hybrid teaching strategy via mobile phone applications in education on college students’ achievement in mathematics. The research divided the students into two groups, an experimental group and a control group. When conducting the test, the research community was taken from students of the Principles of Mathematics course at the university for the second semester of the academic year 2021/2022. The sample was taken from 60 students who were deliberately selected and divided into an experimental study group (30) students who were studied according to the hybrid teaching strategy via mobile phone applications in education and a control group (30) students who were taught in the usual way. The equivalence of the two groups was taken into account according to the variables: the student’s age, intelligence, and grades in previous mathematics courses. An achievement test was prepared, and the data was collected, analyzed, and processed statistically using the (t) test. The results obtained indicated the superiority of the experimental group over the control group, which confirms the positive impact of using hybrid education in teaching mathematics. The implementation of mobile applications indicates the need for professional development activities for teachers, students, and educational administrations in an adequate and thoughtful manner.